A positive electrode sheet, a secondary battery and a preparation method therefor, a battery assembly, a battery pack, an electric device, and a vehicle

CN122950381APending Publication Date: 2026-10-20BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610099028.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-01-23
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]本发明提供一种正极极片、二次电池及其制备方法、电池组件、电池包、用电装置和车辆,用以解决现有技术在高镍正极高电压界面稳定化方面,尚无法在不损伤材料或牺牲性能的前提下,构筑出能长期耐受高电位氧化的稳定保护界面,导致界面阻抗持续增长与电池循环寿命受限的缺陷,实现正极侧界面的长期稳定与整芯性能的综合优化

Benefits of technology

[0056]本发明提供的正极极片在基础正极极片表面构建有一层由含氟添加剂经电化学活化形成的CEI膜,该CEI膜薄而致密,富含LiF及氟化碳结构,作为高效的憎水屏障和离子通道,能够有效抑制高电压(如4.5V)循环下的电解液氧化分解、过渡金属离子溶出及气体析出,从而大幅降低界面阻抗的增长速率,显著提升电池在严苛条件下的循环容量保持率与高温存储后的性能恢复能力;同时,该CEI膜不损害电池的动力学性能,保持了优良的倍率与低温性能。此外,本发明采用的原位电化学活化工艺无需高温步骤,且利用高稳定性的含氟添加剂,在确保效果的同时兼顾了工艺的安全性、可控性与经济性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a positive electrode sheet, a secondary battery, a method for preparing the same, a battery assembly, a battery pack, an electrical device, and a vehicle. The positive electrode sheet comprises a positive electrode material, which includes a positive electrode active material and a positive electrode electrolyte interface film formed on at least a portion of the surface of the positive electrode active material after electrochemical activation treatment. The positive electrode electrolyte interface film, as obtained by X-ray photoelectron spectroscopy (XPS), exhibits at least a first peak in the range of 683-687 eV, a second peak in the range of 688-692 eV, and a third peak in the range of 292-296 eV. The positive electrode sheet provided by this invention has a surface enriched with a specific CEI film. Applying such a positive electrode sheet to a battery can comprehensively improve the cycle life and storage stability of the battery under high voltage and high temperature environments without sacrificing battery kinetic performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a positive electrode sheet, a secondary battery and its preparation method, a battery assembly, a battery pack, an electrical device and a vehicle. Background Technology

[0002] Lithium-ion batteries are developing towards higher energy density, and high-nickel layered cathode materials, such as LiNi... 0.8 Co 0.1 Mn 0.2 O2 (NCM811), for example, is key to achieving this goal due to its high specific capacity. To fully utilize its energy density advantage, such batteries typically require a higher charging cut-off voltage (e.g., ≥4.5 V vs. Li / Li). + However, at high potentials, the surface of high-nickel cathode materials has extremely strong oxidizing properties, which catalyzes the violent oxidative decomposition of the electrolyte. This leads to extreme instability of the cathode-electrolyte interface (CEI) between the cathode and the electrolyte, resulting in a series of problems such as rapid capacity decay, shortened cycle life, gas generation, and deterioration of safety performance.

[0003] To address the aforementioned technical challenges, existing technologies primarily focus on interface stabilization of high-nickel cathodes, and can generally be categorized into the following three technical approaches: (1) Inorganic coating: This approach often uses Al2O3, ZrO2, LiNbO3, Li3PO4, etc., to build an inert barrier on the particle surface through sol-gel or solid-phase methods. Although it can reduce the corrosion caused by electrolyte oxidation and salt decomposition, it usually requires heat treatment at hundreds of degrees Celsius, which can easily induce surface reconstruction, oxygen vacancies and microcracks, leading to increased polarization and limited rate performance. At the same time, the coating uniformity is affected by process fluctuations, and the cost and yield pressure are relatively large.

[0004] (2) Electrolyte additives: This approach involves introducing additives with specific functions into the electrolyte, such as fluoroethylene carbonate (FEC), vinylene carbonate (VC), lithium difluorooxalate borate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI), and tri(trimethylsilyl)phosphite (TMSP). These additives primarily serve the negative electrode or lower potential windows. However, they are prone to over-oxidation or the formation of unstable byproducts at ≥4.4-4.5 V, making it difficult to form a long-term stable, dense, and oxidation-resistant CEI on the surface of the high-nickel positive electrode. Furthermore, the PF5 / HF derivatives in the LiPF6 system will still corrode the positive electrode surface, induce the dissolution of transition metals, and cause secondary damage on the negative electrode side.

[0005] (3) Organic molecule pre-film / surface pretreatment: This approach involves pre-treating the surface of the cathode material with certain organic molecules before electrode preparation or electrolyte injection to improve its initial wettability and form an affinity interface. Although this approach can improve initial wettability and interfacial affinity, common small molecules often have insufficient tolerance under high potential and high temperature conditions, resulting in limited hydrophobicity and chemical stability of the film, making it difficult to continuously suppress electrolyte penetration and acidic species attack.

[0006] In summary, existing technologies face a dilemma when addressing the interfacial stability of high-nickel cathodes at voltages of 4.5 V and above: inorganic coating methods relying on high-temperature processes sacrifice ion transport performance and increase costs; while electrolyte additives and organic pretreatment methods cannot effectively suppress metal dissolution and gaseous side reactions because the film-forming components are susceptible to oxidation and aging on the cathode side. These limitations collectively lead to a rapid increase in interfacial impedance and a severely limited cycle life during long-cycle operation, hindering the commercial application and development of high-energy-density lithium-ion batteries. Summary of the Invention

[0007] This invention provides a positive electrode sheet, a secondary battery and its preparation method, a battery module, a battery pack, an electrical device and a vehicle, to solve the defects of the prior art in the stabilization of the high-voltage interface of high-nickel positive electrodes, which is unable to construct a stable protective interface that can withstand high-potential oxidation for a long time without damaging the materials or sacrificing performance, resulting in continuous growth of interface impedance and limited battery cycle life, and to achieve long-term stability of the positive electrode side interface and comprehensive optimization of the overall cell performance.

[0008] This invention provides a positive electrode sheet, comprising a positive electrode material, the positive electrode material including a positive electrode active material, and a positive electrode electrolyte interface (CEI) film formed on at least a local surface of the positive electrode active material after electrochemical activation treatment; the positive electrode electrolyte interface film, in the XPS spectrum obtained by X-ray photoelectron spectroscopy, has at least a first peak in the range of 683-687 eV, a second peak in the range of 688-692 eV, and a third peak in the range of 292-296 eV.

[0009] In this invention, the first, second, and third peaks are characteristic peaks corresponding to fluorine-containing groups, with the first peak corresponding to LiF and the second and third peaks corresponding to carbon fluoride. The CEI film in the positive electrode provided by this invention possesses the above-mentioned characteristics, resulting in excellent high-voltage stability, superior electrode protection, and stable and efficient ion transport capabilities. Applying such a positive electrode to batteries can simultaneously solve common degradation problems in high-voltage batteries, such as gas evolution, metal dissolution, and impedance surge, without sacrificing battery kinetic performance. This comprehensively improves the cycle life and storage stability of batteries under high voltage and high temperature environments.

[0010] According to the positive electrode sheet of the present invention, the peak position of the first peak is in the range of 685±0.6eV, 685±0.5eV, 685±0.4eV, 685±0.3eV, 685±0.2eV or 685±0.1eV.

[0011] According to the positive electrode sheet of the present invention, the peak position of the third peak is in the range of 294±0.6eV, 294±0.5eV, 294±0.4eV, 294±0.3eV, 294±0.2eV or 294±0.1eV.

[0012] According to the positive electrode sheet of the present invention, the CEI film mainly contains LiF, -CF2- / -CF3-, a small amount of metal fluoride and organic matrix.

[0013] According to the positive electrode sheet of the present invention, the thickness of the positive electrode electrolyte interface film is 3-25 nm, for example, it can be 3 nm, 4 nm, 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, 11 nm, 12 nm, 13 nm, 14 nm, 15 nm, 16 nm, 17 nm, 18 nm, 19 nm, 20 nm, 21 nm, 22 nm, 23 nm, 24 nm or 25 nm. In some specific embodiments, the thickness of the positive electrode electrolyte interface film is 8-24 nm.

[0014] According to the positive electrode sheet of the present invention, the positive active material is selected from one or more of NCM811-based positive electrode materials, NCM8-based positive electrode materials, and NCA-based positive electrode materials.

[0015] NCM8 series cathode materials are a general term for high-nickel ternary materials, specifically referring to a series of materials with a nickel content of around 80% and a combined cobalt and manganese content of 20%. This includes NCM811 series cathode materials, which refer to LiNi cathode materials with a strict nickel-cobalt-manganese molar ratio of 8:1:1. 0.8 Co 0.1 Mn 0.1Based on O2, this material system enhances performance through modification methods such as surface coating, elemental doping, and single crystallization. NCA-based cathode materials are high-nickel cathode materials that do not contain manganese (Mn) and use a small amount of aluminum (Al) to replace some of the cobalt (Co), such as LiNi. 0.8 Co 0.15 Al 0.05 O2.

[0016] Preferably, the positive electrode active material of the present invention is an NCM811-based positive electrode material.

[0017] The present invention also provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode is the aforementioned positive electrode.

[0018] The electrolyte of the present invention can be a conventional 1 M LiPF6 / carbonate system or a mixed salt system containing LiFSI.

[0019] According to the preparation method of the secondary battery of the present invention, a battery cell is constructed, the battery cell comprising a positive electrode active material, a negative electrode sheet, an electrolyte and a fluorine-containing additive; The battery cell is subjected to electrochemical activation treatment, which causes the fluorine-containing additive to react on the surface of the positive electrode active material to form the positive electrode electrolyte interface film. The fluorinated additive is selected from one or more of perfluoroalkyl propylene oxides, wherein the alkyl group is C1-C7 alkyl.

[0020] Preferably, the step of constructing the battery cell is selected from any of the following methods: Method (1): The basic positive electrode sheet is impregnated in an impregnation solution containing the fluorine additive, and after drying, a positive electrode sheet containing the fluorine additive is obtained, which is then assembled with a negative electrode sheet and an electrolyte. Method (2): Mix the positive electrode active material with the fluorine-containing additive to prepare a positive electrode sheet containing the fluorine-containing additive, and then assemble it with the negative electrode sheet and electrolyte; Method (3): Add the fluorine-containing additive to the electrolyte and then assemble it with the positive electrode and the negative electrode.

[0021] Preferably, the fluorinated additive is selected from perfluorohexylpropane oxide (hereinafter referred to as PFHPO), which has both a perfluoroalkyl structure with high oxidation stability and stress-driven epoxy active sites. The mechanism of action of PFHPO may be as follows: PFHPO undergoes adsorption and ring-opening reactions with residual basic species (LiOH, Li2CO3) and Lewis acid / metal sites on the surface of NCM811 to form an organic fluorinated layer anchored on the particle surface; under the subsequent high initial charge potential, PFHPO further undergoes directional electrochemical decomposition to generate LiF, metal fluorides (M-Fx, x is 1, 2 or 3) and polymer phases containing -CFx- (x is 2 or 3), constructing a fluorine-rich, dense, hydrophobic and oxidation-resistant CEI film, preventing direct contact between the electrolyte and the positive electrode active surface.

[0022] According to the preparation method of the secondary battery of the present invention, in method (1), the preparation method includes the following steps: placing the basic positive electrode sheet in an impregnation solution containing fluorine additives for impregnation, taking it out and drying it, and then forming a battery unit with an electrolyte and a negative electrode sheet for electrochemical activation treatment to form a positive electrode electrolyte interface film on the surface of the positive electrode active material of the basic positive electrode sheet.

[0023] This invention employs a synergistic process of impregnating a base positive electrode sheet with a fluorinated additive and subsequent electrochemical activation to construct a thin, dense, and stable CEI film rich in LiF and fluorinated carbon species in situ on the surface of the positive electrode active material. This film acts as a highly efficient hydrophobic barrier, significantly inhibiting the oxidative decomposition of the electrolyte and the dissolution of transition metal ions under high voltage (4.5V), thereby effectively reducing gas generation, lowering interfacial impedance growth, and significantly improving the cycle life and storage stability of the battery under harsh conditions. Furthermore, this process eliminates the need for high-temperature treatment and utilizes highly stable fluorinated additives, improving battery performance while ensuring production safety and feasibility.

[0024] According to the preparation method of the secondary battery of the present invention, in method (1), during the impregnation process, the liquid-to-solid ratio is 5-50 mL / g, the temperature is 20-60℃, and the time is 0.5-6 h. Precisely limiting the liquid-to-solid ratio, temperature, and time during the impregnation process is beneficial to ensure uniform penetration and appropriate reaction of the fluorine-containing additive in the positive electrode, thereby laying the foundation for the subsequent electrochemical activation step to form a stable, uniform, and high-performance CEI film. If the liquid-to-solid ratio is less than 5 mL / g, it will cause uneven wetting of the electrode, and the surface of the active material will not be able to obtain a consistent fluorine source precursor coverage, which will lead to defects and uneven protection in the formed CEI film; if the liquid-to-solid ratio is greater than 50 mL / g, it will lead to solvent waste, excessive swelling of the electrode, and increased subsequent drying load and difficulty.

[0025] In this invention, the liquid-to-solid ratio is 5-50 mL / g, for example, it can be 5 mL / g, 10 mL / g, 20 mL / g, 30 mL / g, 40 mL / g, or 50 mL / g, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range; the temperature is 20-60℃, for example, it can be 20℃, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃, or 60℃, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range; the time is 0.5-6h, for example, it can be 0.5h, 1h, 2h, 3h, 4h, 5h, or 6h, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0026] According to the preparation method of the secondary battery of the present invention, the volume fraction of the fluorinated additive in the impregnation solution is 30-100%, for example, it can be 30%, 40%, 50%, 60%, 70%, 80%, 90% or 100%, etc., and specific values ​​between the above values. Due to space limitations and for the sake of brevity, the present invention will not exhaustively list the specific values ​​included in the range, but preferably it is 70-100%.

[0027] The present invention limits the volume fraction of the fluorinated additive in the impregnation solution to a reasonable range, which is beneficial to accurately control its effective adsorption concentration on the electrode surface. This ensures the formation of a high-quality CEI film while avoiding the increased cost or subsequent side reaction risks caused by excessive solvent.

[0028] Preferably, the impregnation solution further includes one or both of an inert diluent and a wetting agent. The diluent is selected from one or more hydrofluoroether diluents, and the wetting agent is selected from one or more HFE wetting agents and perfluorohexane. Hydrofluoroether diluents mainly include several series such as HFE-7100 / 7200, HFE-7500, and HFE-347, and their perfluoropolyether derivatives, for example, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0029] According to the preparation method of the secondary battery of the present invention, in method (2), the preparation method includes the following steps: mixing positive electrode active material and fluorine-containing additive and drying to obtain modified positive electrode active material; using the modified positive electrode active material as raw material to prepare a non-film positive electrode sheet; and then combining the non-film positive electrode sheet with electrolyte and negative electrode sheet to form a battery unit for electrochemical activation treatment to form a positive electrode electrolyte interface film on the surface of the positive electrode active material.

[0030] According to the preparation method of the secondary battery of the present invention, in method (2), the weight ratio of the positive electrode active material to the volume ratio of the fluorinated additive is 1:(5-20), for example, it can be 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19 or 1:20, etc., and the specific values ​​between the above values ​​are not exhaustively listed in the present invention due to space limitations and for the sake of brevity.

[0031] This invention limits the weight ratio of the positive electrode active material to the volume ratio of the fluorinated additive within a reasonable range. This ensures that each active material particle receives adequate and uniform solvent coverage, resulting in a consistent and stable high-quality CEI film after electrochemical activation. This optimizes solvent utilization efficiency while maintaining excellent battery performance. If the weight ratio of the positive electrode active material to the volume ratio of the fluorinated additive is greater than 1:5, sufficient and uniform wetting and fluorine source coverage of the active material particles cannot be ensured. This leads to discontinuous, defective, or locally thin CEI films, weakening their protective barrier effect and failing to effectively suppress interfacial side reactions and metal dissolution under high voltage, thus affecting the long-term cycle stability of the battery. If the weight ratio of the positive electrode active material to the volume ratio of the fluorinated additive is greater than 1:20, excessive fluorine adsorbed on the active material surface will easily form an excessively thick and unevenly dense CEI film during subsequent electrochemical activation. This increases lithium-ion migration resistance, impairs rate performance, and also wastes solvent and increases costs.

[0032] According to the preparation method of the secondary battery of the present invention, in the method (2), the mixing temperature is 25-60°C and the time is 0.5-4h.

[0033] This invention limits the mixing temperature and time within a reasonable range, which is beneficial for achieving thermodynamic and kinetic equilibrium. A suitable temperature (such as room temperature to moderate heating) can maintain the chemical stability of the fluorinated additive and regulate its viscosity and volatility, thereby promoting the full and uniform penetration of the solvent into the electrode pores; while precise time control can ensure that the surface of the active material is adequately wetted and initially adsorbed, avoiding excessive solvent volatilization, decomposition, or unnecessary pre-reaction.

[0034] In this invention, the mixing temperature is 25-60℃, for example, it can be 25℃, 30℃, 35℃, 40℃, 45℃, 50℃, 55℃ or 60℃, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range; the mixing time is 0.5-4h, for example, it can be 0.5h, 1h, 2h, 3h or 4h, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0035] According to the method for preparing a secondary battery of the present invention, in step (2), the drying temperature is 80-120°C and the time is 2-8 hours. Stepwise heating may be used if necessary to avoid thermal stress on the binder.

[0036] In this invention, the drying temperature is 80-120℃, for example, it can be 80℃, 85℃, 90℃, 95℃, 100℃, 105℃, 110℃, 115℃ or 120℃, etc., and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range; the drying time is 2-8h, for example, it can be 2h, 3h, 4h, 5h, 6h, 7h or 8h, and specific values ​​between the above points. Due to space limitations and for the sake of brevity, this invention will not exhaustively list the specific values ​​included in the range.

[0037] According to the preparation method of the secondary battery of the present invention, in the method (3), the preparation method includes the following steps: mixing the fluorine-containing additive with the electrolyte and then combining it with the positive electrode active material and the negative electrode sheet to form a battery cell for electrochemical activation treatment, so as to form a positive electrode electrolyte interface film on the surface of the positive electrode active material.

[0038] This invention adds a fluorine-containing additive to the electrolyte as a film-forming precursor, and, in conjunction with short-time impregnation or pre-spraying of the electrode, generates in-situ fluorine-rich CEI during the first charge stage, thereby effectively improving the cycle stability and interfacial chemical stability of the battery under high voltage. This invention is suitable for production lines where an additional impregnation process cannot be set up.

[0039] According to the preparation method of the secondary battery of the present invention, in method (3), the amount of the fluorine-containing additive is 0.1-5% of the mass of the electrolyte, for example, it can be 0.1%, 0.5%, 0.8%, 1%, 2%, 3%, 4% or 5%, etc., and the specific values ​​between the above values ​​are not exhaustively listed in the present invention due to space limitations and for the sake of brevity.

[0040] This invention limits the amount of fluorine-containing additive to a reasonable percentage of the mass of the base electrolyte. This facilitates the provision of a sufficient and uniform fluorine source during electrochemical activation to construct a stable CEI film, while avoiding the negative impact of excessive addition on the electrolyte's ionic conductivity and overall electrochemical performance. If the amount of fluorine-containing additive is less than 0.1% of the mass of the base electrolyte, a stable CEI film cannot be formed. If the amount of fluorine-containing additive is greater than 5% of the mass of the base electrolyte, it will lead to excessively high electrolyte viscosity and a significant decrease in ionic conductivity. It may also trigger excessive side reactions on the positive electrode surface or form an excessively thick CEI film with high impedance, ultimately resulting in increased battery internal resistance and deterioration of capacity and rate performance.

[0041] The present invention also provides a battery assembly including the aforementioned secondary battery.

[0042] The present invention also provides a battery pack, including the above-described secondary battery or the above-described battery assembly.

[0043] The present invention also provides an electrical device, including at least one of the above-described secondary battery, the above-described battery assembly, or the above-described battery pack.

[0044] The electrical device includes, but is not limited to: 1. Vehicles: such as electric ships, electric aircraft (such as eVTOL flying cars, drones, etc.).

[0045] 2. Energy storage system: Energy storage power stations for residential or commercial use (such as household energy storage cabinets and containerized energy storage systems).

[0046] As a supporting energy storage device for renewable energy (such as solar and wind power) power generation, it is used for grid peak shaving, off-grid power supply, etc.

[0047] Uninterruptible power supply (UPS) for communication base stations and data centers.

[0048] 3. Portable and consumer electronic devices: Mobile phones, laptops, tablets, wearable devices (smartwatches, wristbands), wireless headphones, digital cameras, camcorders, portable game consoles, power tools (such as electric drills, chainsaws), drones, etc.

[0049] 4. Other electrical equipment: Home appliances (such as robot vacuum cleaners and electric gardening tools).

[0050] Medical equipment (such as portable monitors, electric wheelchairs).

[0051] Energy storage power source for spacecraft and artificial satellites.

[0052] It should be understood that the above examples are merely illustrative, and any device that uses the secondary battery, battery assembly or battery pack described in this invention to provide electrical energy should fall within the scope of the electrical devices of this invention.

[0053] The present invention also provides a vehicle comprising at least one of the above-described secondary battery, the above-described battery assembly, or the above-described battery pack.

[0054] The vehicle may be an electric vehicle or a hybrid vehicle that relies on a battery pack as its sole or partial power source. For example: Road vehicles: such as battery electric vehicles (BEV), plug-in hybrid electric vehicles (PHEV), range-extended electric vehicles (EREV), electric motorcycles, electric bicycles, electric scooters, electric trucks, electric buses, etc.

[0055] Special vehicles: such as electric construction machinery (excavators, loaders), electric agricultural machinery, electric golf carts, electric sanitation vehicles, etc.

[0056] The positive electrode provided by this invention has a CEI film formed by electrochemical activation of fluorine-containing additives on the surface of a basic positive electrode. This CEI film is thin and dense, rich in LiF and fluorinated carbon structures, and acts as a highly efficient hydrophobic barrier and ion channel. It can effectively inhibit the oxidative decomposition of electrolyte, dissolution of transition metal ions, and gas evolution under high voltage (e.g., 4.5V) cycling, thereby significantly reducing the growth rate of interfacial impedance and significantly improving the battery's cycle capacity retention rate under harsh conditions and its performance recovery ability after high-temperature storage. At the same time, this CEI film does not impair the battery's kinetic performance and maintains excellent rate capability and low-temperature performance. In addition, the in-situ electrochemical activation process used in this invention does not require a high-temperature step and utilizes highly stable fluorine-containing additives, ensuring the effectiveness while taking into account the safety, controllability, and economy of the process. Attached Figure Description

[0057] To more clearly illustrate the technical solutions in this invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0058] Figure 1 This is an XPS image of the CEI film on the surface of the positive electrode in the secondary battery provided in Embodiment 1 of the present invention.

[0059] Figure 2 This is an ICP-MS image of the CEI film on the surface of the positive electrode in the secondary battery provided in Embodiment 1 of the present invention.

[0060] Figure 3 This is a TEM image of the CEI film on the surface of the positive electrode in the secondary battery provided in Embodiment 16 of the present invention.

[0061] Figure 4 This is an ICP-MS image of the CEI film on the surface of the positive electrode in the secondary battery provided in Embodiment 16 of the present invention. Detailed Implementation

[0062] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0063] Example 1 This embodiment provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte. The preparation method of the secondary battery includes the following steps: A positive electrode slurry was prepared by combining 80g NCM811, 10g Super P, 10g PVDF binder, and 100g N-methylpyrrolidone solvent. The positive electrode slurry was then coated onto aluminum foil using conventional processes, dried, and rolled into shape.

[0064] The electrode was purged with room temperature inert gas for 10 min to remove surface liquid, and then dried under vacuum (≤100 Pa) at 90°C for 2 h to remove moisture.

[0065] The dried NCM811 positive electrode sheet was immersed in PFHPO2 solution with a purity ≥98% at 25℃ with a liquid-to-solid ratio of 5mL / g for 2 hours, then removed and dried; vacuum dried at 90℃ for 2 hours; and then assembled into a coin cell with a graphite negative electrode sheet and electrolyte for electrochemical activation treatment to form a CEI film on the surface of the NCM811 material. The electrolyte composition was 1M LiPF6, EC:EMC:DEC=1:1:1; the electrochemical activation treatment conditions were: one charge-discharge cycle at a rate of 0.1C.

[0066] like Figure 1 As shown, XPS revealed a LiF peak (~685 eV) and a –CFx peak (~688–692 eV) detected at F 1s, and a –CF2 / –CF3 peak (294 ± 0.2 eV) detected at C 1s. Figure 2 As shown in the figure, ICP-MS reveals that the surface stability of Ni / Co / Mn valence states is enhanced after being left to stand at high temperature.

[0067] Example 2 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that the liquid-to-solid ratio of NCM811 positive electrode to PFHPO is 10 mL / g.

[0068] Example 3 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that the liquid-to-solid ratio of NCM811 positive electrode to PFHPO is 20 mL / g.

[0069] Example 4 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 1 in that the liquid-to-solid ratio of NCM811 positive electrode to PFHPO is 30 mL / g.

[0070] Example 5 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 1 in that the liquid-to-solid ratio of NCM811 positive electrode to PFHPO is 50 mL / g.

[0071] Example 6 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that the immersion temperature is 60°C and the time is 1 hour.

[0072] Example 7 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that the immersion temperature is 20°C and the time is 3 hours.

[0073] Example 8 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that the immersion temperature is 40°C and the time is 1.5h.

[0074] Example 9 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that: the impregnation solution also includes an inert diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume fraction of PFHPO in the impregnation solution is 30%.

[0075] Example 10 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 1 in that: the impregnation solution also includes an inert diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, and the volume fraction of PFHPO in the impregnation solution is 70%.

[0076] Comparative Example 1 This comparative example provides a secondary battery whose preparation method differs from that of Example 1 in that perfluorooctylpropene oxide is used instead of PFHPO.

[0077] Example 11 This embodiment provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte. The preparation method of the secondary battery includes the following steps: NCM811 powder and PFHPO were stirred at 40℃ for 2 hours at a ratio of 1:10 (g:mL), filtered, and vacuum dried at 100℃ for 4 hours to obtain a modified positive electrode active material. 80g NCM811, 10g Super P, 10g binder PVDF and 100g solvent N-methylpyrrolidone were used to prepare a positive electrode slurry. The positive electrode slurry was coated onto aluminum foil according to conventional process, dried and rolled to obtain an unfilmed positive electrode sheet.

[0078] The unfilmed positive electrode, along with the electrolyte and graphite negative electrode, is then subjected to electrochemical activation treatment to form a CEI film on the surface of the NCM811 material. The electrolyte composition is 1M LiPF6, with EC:EMC:DEC = 1:1:1. The electrochemical activation treatment conditions are: one charge-discharge cycle at a rate of 0.1C.

[0079] Example 12 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 11 in that NCM811 powder and PFHPO are mixed at a ratio of 1:5.

[0080] Example 13 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 11 in that NCM811 powder and PFHPO are mixed at a ratio of 1:20.

[0081] Example 14 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 11 in that: NCM811 powder is stirred at 25°C for 4 hours.

[0082] Example 15 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 11 in that: NCM811 powder is stirred at 60°C for 1 hour.

[0083] Example 16 This embodiment provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte. The preparation method of the secondary battery includes the following steps: A positive electrode slurry was prepared by combining 80g NCM811, 10g Super P, 10g PVDF binder, and 100g N-methylpyrrolidone solvent. The positive electrode slurry was coated onto aluminum foil using conventional processes, dried, and rolled into shape. The electrode was then purged with inert gas at room temperature for 10 minutes to remove surface liquid, and then dried at 90°C under vacuum (≤100 Pa) for 2 hours to remove moisture, resulting in an uncoated NCM811 positive electrode.

[0084] PFHPO was mixed with a basic electrolyte and then combined with an unfilmed positive electrode and a graphite negative electrode to form a battery. Electrochemical activation treatment was then performed to form a CEI film on the surface of NCM811 material. The basic electrolyte composition was 1M LiPF6, EC:EMC:DEC = 1:1:1, and the amount of PFHPO added was 0.1% of the basic electrolyte. The electrochemical activation treatment conditions were: one charge-discharge cycle at a rate of 0.1C.

[0085] like Figure 3 As shown, TEM revealed a uniform and continuous nanoscale CEI film on the surface of NCM811 particles. Figure 4 As shown, ICP-MS revealed a decrease in Ni / Co / Mn dissolution after standing at high temperature.

[0086] Example 17 This embodiment provides a secondary battery, the only difference between the preparation method of the secondary battery and that of Example 16 is that the amount of PFHPO added is 0.5% of the base electrolyte.

[0087] Example 18 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 16 only in that the amount of PFHPO added is 1% of the base electrolyte.

[0088] Example 19 This embodiment provides a secondary battery, the preparation method of which differs from that of Example 16 only in that the amount of PFHPO added is 2% of the base electrolyte.

[0089] Example 20 This embodiment provides a secondary battery, the preparation method of which differs from that of Embodiment 16 only in that the amount of PFHPO added is 5% of the base electrolyte.

[0090] Performance testing The secondary batteries of the examples and comparative examples were subjected to the following performance tests, and the test results are shown in Table 1 below.

[0091] Test Methods: At 25℃, the battery was charged and discharged at a 1C rate for 100 cycles. After each cycle, the EIS impedance was measured, and the battery was disassembled. TEM was used to characterize the CEI film thickness on the surface of the NCM811 particles. Cycling at 25℃ at 1C until the battery capacity decreased to 80% of its initial capacity was defined as the battery's cycle performance. At 25℃, the battery was cycled 10 times at 0.5C, 1C, 2C, 3C, 4C, and 5C rates respectively. The ratio of the average capacity utilization of 10 cycles at 5C to the average capacity utilization of 10 cycles at 0.5C was taken as the rate performance. At 45℃, the battery was cycled at 1C until its capacity decreased to 80% of its initial capacity, which was defined as the battery's high-temperature performance.

[0092] Table 1 CEI film thickness (nm) EIS impedance (mΩ) Cyclic performance (cycles) Ratio performance High-temperature performance (circle) Example 1 15 20 1000 0.68 800 Example 2 16 22 960 0.66 770 Example 3 18 25 920 0.64 730 Example 4 20 29 860 0.61 680 Example 5 24 35 780 0.57 610 Example 6 17 23 940 0.65 740 Example 7 16 21 980 0.67 790 Example 8 16 21 970 0.66 780 Example 9 12 26 900 0.62 700 Example 10 14 22 960 0.66 760 Example 11 13 19 980 0.69 820 Example 12 10 24 910 0.64 740 Example 13 18 28 880 0.61 690 Example 14 14 20 990 0.68 810 Example 15 15 22 950 0.66 760 Example 16 8 27 880 0.6 650 Example 17 12 23 940 0.64 730 Example 18 14 21 980 0.66 780 Example 19 16 22 960 0.65 760 Example 20 20 28 860 0.6 650 Comparative Example 1 28 48 520 0.45 380 Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positive electrode sheet, comprising a positive electrode material, characterized in that, The positive electrode material includes a positive electrode active material and a positive electrode electrolyte interface film formed on at least a local surface of the positive electrode active material after electrochemical activation treatment; the positive electrode electrolyte interface film has at least a first peak in the range of 683-687 eV, a second peak in the range of 688-692 eV, and a third peak in the range of 292-296 eV in the XPS spectrum obtained by X-ray photoelectron spectroscopy.

2. The positive electrode sheet according to claim 1, characterized in that, The peak position of the first peak is within the range of 685±0.6eV, 685±0.5eV, 685±0.4eV, 685±0.3eV, 685±0.2eV or 685±0.1eV; And / or, the peak position of the third peak is in the range of 294±0.6eV, 294±0.5eV, 294±0.4eV, 294±0.3eV, 294±0.2eV or 294±0.1eV.

3. The positive electrode sheet according to claim 1 or 2, characterized in that, The thickness of the positive electrode electrolyte interface film is 3-25 nm.

4. The positive electrode sheet according to any one of claims 1-3, characterized in that, The positive electrode active material is selected from one or more of NCM8-based positive electrode materials and NCA-based positive electrode materials.

5. A secondary battery, comprising a positive electrode, a negative electrode, and an electrolyte, characterized in that, The positive electrode sheet is the positive electrode sheet according to any one of claims 1-4.

6. The method for preparing the secondary battery according to claim 5, characterized in that, The steps include: constructing a battery cell, wherein the battery cell includes a positive electrode active material, a negative electrode sheet, an electrolyte, and a fluorine-containing additive; The battery cell is subjected to electrochemical activation treatment, which causes the fluorine-containing additive to react on the surface of the positive electrode active material to form the positive electrode electrolyte interface film. The fluorinated additive is selected from one or more of perfluoroalkyl propylene oxides, wherein the alkyl group is C1-C7 alkyl. Preferably, the step of constructing the battery cell is selected from any of the following methods: (1): The basic positive electrode sheet is impregnated in an impregnation solution containing the fluorine additive, and after drying, a positive electrode sheet containing the fluorine additive is obtained, which is then assembled with a negative electrode sheet and an electrolyte. (2): The positive electrode active material is mixed with the fluorine-containing additive to prepare a positive electrode sheet containing the fluorine-containing additive, and then assembled with the negative electrode sheet and electrolyte; (3): Add the fluorine-containing additive to the electrolyte and then assemble it with the positive electrode and the negative electrode.

7. The method for preparing a secondary battery according to claim 6, characterized in that, In method (1), during the impregnation process, the liquid-to-solid ratio is 5-50 mL / g, the temperature is 20-60℃, and the time is 0.5-6 h.

8. The method for preparing a secondary battery according to claim 6 or 7, characterized in that, In method (1), the volume fraction of the fluorinated additive in the impregnation solution is 30-100%; Preferably, the impregnation solution further includes one or two of an inert diluent or a wetting agent, wherein the diluent is selected from one or more hydrofluoroether diluents, and the wetting agent is selected from one or more HFE wetting agents and perfluorohexane.

9. The method for preparing a secondary battery according to claim 6, characterized in that, In method (2), the weight ratio of the positive electrode active material to the volume ratio of the fluorinated additive is 1:(5-20). And / or, the mixing temperature is 25-60°C, and the time is 0.5-4h.

10. The method for preparing a secondary battery according to claim 6, characterized in that, In method (3), the amount of the fluorine-containing additive is 0.1-5% of the mass of the electrolyte.

11. A battery assembly, characterized in that, Includes the secondary battery as described in claim 5.

12. A battery pack, characterized in that, It includes the secondary battery as described in claim 5 or the battery assembly as described in claim 11.

13. An electrical appliance, characterized in that, It includes at least one of the secondary battery of claim 5, the battery assembly of claim 11, or the battery pack of claim 12.

14. A vehicle, characterized in that, It includes at least one of the secondary battery of claim 5, the battery assembly of claim 11, and the battery pack of claim 12.